Kosmologi Islam Kasultanan Ngayogyakarta Hadiningrat - Zuhriyah, Lailatuzz (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This article scrutinizes the concept of cosmology held by the Kasultanan Ngayogyakarta Hadiningrat. The writer observes that the process of islamization in Java island has, more or less, influenced the mindset of javanese people, including the people of Kasultanan Ngayogyakarta Hadiningrat. Once islamized, the Sultanate has adapted islamic teachings and made them as a part of its cultural mindset. In this stage, the acculturation has been done succesfully. Such acculturation has subsequently influenced their view on cosmology, which is different from?and does not reflect?Hinduism?s and Buddhism?s cosmology. The use of title Senopati ing Alaga Sayidin Panatagama Khalîfatullah by the sultans of Yogyakarta clearly indicates that they respect the old concept. Since the advent of Islam, javanese culture, including the culture of the Sultanate of Yogyakarta, has been subsequently islamized.